A systematic mixed studies review of health behaviour change interventions in colorectal cancer survivors. (2nd May 2020) - Sweeney‐Magee, Molly; Moustaqim‐Barrette, Amina; Gotay, Carolyn; Dummer, Trevor
Abstract: Aims: To explore available health behaviour change interventions in improving key health behaviours in colorectal cancer survivors and patient perspectives about these interventions. Design: A systematic mixed studies review was conducted. Data Sources: Databases searched included Ovid Medline, Ovid Embase, EBSCO PsychoInfo and EBSCO CINAHL. A grey literature search was also completed using Google Scholar and the TRIP database. Identified studies were published between 2003 – 2018. Review methods: A parallel‐results convergent synthesis design using narrative syntheses was used. Data analysis was conducted following a process of constant comparison. Quality appraisal was conducted using recognized tools appropriate to different study designs. Results: Sixteen unique studies were identified from an initial search of 354 records. There was a pattern of successful physical activity and dietary change associated with behaviour change interventions of varying intensity, modality and length, but sparse description of intervention content was common. Participants preferred clear explanations of health behaviour importance and for interventions to be administered in sessions either with, or led by, other patients. Conclusion: The available evidence tentatively suggests that behaviour change interventions can improve the health behaviours of colorectal cancer survivors. However, more research focused on identifying key intervention elements is needed. Patients indicated clear preferences for specific intervention content and delivery, but further research is needed to allow for the appropriate incorporation of patient preferences into the design of such interventions. Impact: This review highlights the potential for interventions to improve health behaviours evidenced to influence short and long‐term health outcomes in colorectal cancer survivors. However, the examination of the impact of these interventions and patient perspectives indicated a paucity of research. This is an important finding in demonstrating additional research is necessary to improve the support available to a growing group of patients with complex health needs. Abstract : 目的: 探讨现有的健康行为改变干预措施, 以改善结直肠癌幸存者的关键健康行为, 以及患者对此类干预措施的看法。 设计: 开展了一项系统的混合研究评估。 数据来源: 检索数据库包括Ovid Medline、Ovid Embase、EBSCO Psychino和EBSCO CINAHL。同时使用谷歌学术搜索和TRIP数据库完成了灰色文献检索。所选取的研究均发表于2003年至2018年间。 评估方法: 采用了使用叙事综合汇总的平行结果汇集综合设计。完成持续比较之后, 开展数据分析工作。质量评估使用适合不同研究设计的公认工具进行。 结果: 通过对354条记录的初步检索, 共选取了16项独特的研究。其中有一种成功的体力活动和饮食改变的模式, 与行为改变干预措施的不同强度、方式和时间长短有关, 但对干预内容的描述很少。参与者倾向于明确说明健康行为的重要性, 并倾向于与其他患者一起或在由其他患者带领的项目中实施干预措施。 结论: 现有证据初步表明, 行为改变干预措施可以改善结直肠癌幸存者的健康行为。然而, 还需开展更多侧重于确定关键干预要素的研究。患者对具体干预内容和实施方式表现出明确的偏好, 但仍需进一步研究, 以便将患者的偏好适当纳入此类干预措施的设计当中。 影响: 本项评估工作着重研究干预措施改善健康行为的潜力, 且此类干预措施证明会影响结直肠癌幸存者的短期和长期健康结果。然而, 探讨此类干预措施的影响以及病人看法的研究较为欠缺。这项发现十分重要, 表明有必要进行更多的研究, 以改进对越来越多的具有复杂健康需求的患者的支持帮助。